2018
DOI: 10.1542/peds.2018-1042
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Medication Use Among Children and Adolescents in the United States

Abstract: Many US children and adolescents use prescription medications with nearly 1 in 12 concurrent users of prescription medications potentially at risk for a major DDI. Efforts to prevent adverse drug events in children and adolescents should consider the role of interacting drug combinations, especially among adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…C ytochrome P450 2C19 (CYP2C19) metabolizes multiple selective serotonin reuptake inhibitors (SSRIs) (Wang et al 2001;Chang et al 2014;Steere et al 2015), including sertraline, citalopram, and its s-enantiomer, escitalopram. Both escitalopram and sertraline are FDA approved for pediatric use, effectively treat anxiety (March et al 1998;Rynn et al 2001;Walkup et al 2008) and depressive disorders ) in youth, and are commonly prescribed to pediatric patients (Qato et al 2018). To date, more than two dozen variants in the CYP2C19 gene have been identified, and these are associated with varying metabolic activity and include loss-of-function alleles (e.g., null alleles *2-*9) as well as alleles with increased activity (e.g., *17).…”
Section: Introductionmentioning
confidence: 99%
“…C ytochrome P450 2C19 (CYP2C19) metabolizes multiple selective serotonin reuptake inhibitors (SSRIs) (Wang et al 2001;Chang et al 2014;Steere et al 2015), including sertraline, citalopram, and its s-enantiomer, escitalopram. Both escitalopram and sertraline are FDA approved for pediatric use, effectively treat anxiety (March et al 1998;Rynn et al 2001;Walkup et al 2008) and depressive disorders ) in youth, and are commonly prescribed to pediatric patients (Qato et al 2018). To date, more than two dozen variants in the CYP2C19 gene have been identified, and these are associated with varying metabolic activity and include loss-of-function alleles (e.g., null alleles *2-*9) as well as alleles with increased activity (e.g., *17).…”
Section: Introductionmentioning
confidence: 99%
“…Data on prescription medication use were available for 38,277 children and adolescents from 1999 to 2014, and Hales et al 13 found that the overall use of any prescription medication in the past 30 days was 21.9%. During 2013-2014, Qato et al 14 found that 19.8% of children and adolescents were prescribed at least 1 medication, and 7.5% used multiple medications. Rieder 15 reported on a population of 1 million Canadian children and noted that about 20% of all prescriptions were written for 70% of patients, which suggested that patients with complex or chronic diseases frequently receive polytherapy.…”
Section: Introductionmentioning
confidence: 99%
“…1 Most prescriptions are for short-term antibiotics; but many are for longer-term use medications that are used to treat chronic health conditions. [1][2][3] The use of chronic medications (CMs) is not without risk and presents a management challenge in both outpatient and community settings due to the time and effort required to review, reconcile, and monitor CM use. [4][5][6][7][8][9][10][11] The National Academy of Sciences has designated the outpatient environment as a high-priority area for medication safety in children.…”
mentioning
confidence: 99%